2020
DOI: 10.3390/diagnostics10060353
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Tear Lipid Film Thickness Based on a Reflected Placido Disk Tear Film Analyzer

Abstract: This study aims at determining the thickness of the tear lipid layer (LL) observed from a placido-disc-based tear film analyzer. We prospectively collected reflections of placido-disk LL images using a tear film analyzer (Keratograph® 5M, Oculus) from subjects with dry eye symptoms. The LL thickness (LLT) over the inferior half of the cornea was estimated with the use of interference color analysis and the preprocessing of images with and without ring segmentation were obtained and analyzed. Moreover, LLTs bef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 20 publications
(24 reference statements)
0
10
0
Order By: Relevance
“…Comparison of two different image analysis methods using a generalized linear model showed that there was a high correlation between the two techniques [36]. The authors concluded that the simple technique was sufficient for evaluation of tear film lipid layer thickness.…”
Section: Interferometry and Slit-lamp Imagesmentioning
confidence: 98%
See 2 more Smart Citations
“…Comparison of two different image analysis methods using a generalized linear model showed that there was a high correlation between the two techniques [36]. The authors concluded that the simple technique was sufficient for evaluation of tear film lipid layer thickness.…”
Section: Interferometry and Slit-lamp Imagesmentioning
confidence: 98%
“…It is difficult to compare the studies due to different applications and evaluation metrics. Despite promising results, most of the studies [60,59,55,52,34,35,50,36,49,61,48] did not evaluate their systems on external data. The systems should be tested on independent data before they can be considered for clinical application.…”
Section: Interferometry and Slit-lamp Imagesmentioning
confidence: 99%
See 1 more Smart Citation
“…Interferometry is a useful tool that gives a snapshot of the status of the tear film lipid layer, which can be used to aid diagnosis of DED. Machine learning systems have been applied to interferometry and slit-lamp images for lipid layer classification based on morphological properties [60,59,55,54,52,34,35], estimation of the lipid layer thickness [50,36], diagnosis of DED [49,47], determination of ocular redness [61] and estimation of tear meniscus height [48,29].…”
Section: Interferometry and Slit-lamp Imagesmentioning
confidence: 99%
“…The systems should be tested on independent data before they can be considered for clinical application. Moreover, some studies were small [61,36] or pilots [48,29],…”
Section: Interferometry and Slit-lamp Imagesmentioning
confidence: 99%